'Our combined voices are a chorus': grief and survivance in Linda Hogan's Solar Storms. Issue 3 (4th March 2021) - Castor, Laura
ABSTRACT: While Linda Hogan scholars generally agree that in her literature of environmental justice, grieving the effects of colonised territory and culture can motivate characters to confront oppressive authority figures, scholars have not considered how representations of grief in Hogan's novels are themselves significant political acts worthy of analysis. In this article, I argue that Hogan's narrator Angel in her novel Solar Storms shows that grieving is central to Native survivance and environmental justice. In this essay, I utilise a theoretical framework based on the concepts of Native survivance and grievability to suggest how Hogan's novel uses narrative perspective and imagery to represent the role of grief in transforming victimry to survivance for the intergenerational political community of the novel. In addition, I situate the historical James Bay Project in the context of the environmental justice work of Solar Storms .